PEMANFAATAN BERBAGAI SENYAWA NITRIL DAN PRODUK DEGRADASINYA SEBAGAI SUBSTRAT UNTUK PERTUMBUHAN ISOLAT BAKTERI TP - Supriyati, Dyah; Sunarko, Bambang (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Our experiments showed that bacterial isolate TP was able to grow on acetonitrile, butyronitrile and propionitrile as sole sources of carbon, energy and nitrogen, but not on acrylonitrile dan benzonitrile. Besides on nitriles, isolate TP could grow on acetamide,propionamide, benzamide and nicotinamide, but not on acrylamide. However, none of the tested carboxylic acids could be used as growth subtrate for bacterial isolate TP. The best growth substrates of isolate TP were butyronitrile (CH3-CH2-CH2-CN) and propionamide (CH3-CH2-CONH2). When isolate TP grew on butyronitrile, the highest biomass concentration, the doubling-time (td), and the specific growth rate1(n) were 8.99 gram cell dry weight/liter, 4.8 h and 0.144 h , and when grew on propionamide were 4.57 gram cell dry weight/liter, 5.7 h and10.122 h